2003
DOI: 10.1088/0960-1317/13/3/303
|View full text |Cite
|
Sign up to set email alerts
|

Tapered LIGA HARMs

Abstract: The standard LIGA process takes advantage of the use of x-ray lithography to produce mold inserts with nearly vertical sidewall; the typical slope of patterns produced by x-ray lithography of polymethylmethacrylate is 0.1%. This lack of significant taper (draft angle) greatly increases the difficulty associated with ejecting parts during demolding. In this paper, a procedure is described to fabricate a mold insert with tapered features having a height of approximately 1 mm and lateral dimensions of approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 8 publications
1
36
0
Order By: Relevance
“…A standard Cr mask with different patterns as former was then positioned underneath the substrate before exposure same time prevent the microstructures of mold from being damaged. There have been some efforts to achieve this task, for instance utilizing small mechanical librations of mask and substrate based on exposure systems or a corresponding slight movement of the effective light source position in the exposure system by means of a librating mirror (Tabata et al 2002;Turner et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…A standard Cr mask with different patterns as former was then positioned underneath the substrate before exposure same time prevent the microstructures of mold from being damaged. There have been some efforts to achieve this task, for instance utilizing small mechanical librations of mask and substrate based on exposure systems or a corresponding slight movement of the effective light source position in the exposure system by means of a librating mirror (Tabata et al 2002;Turner et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…A method to overcome the limitation in feature height is the use of X-ray lithography and pursue inclined exposure leading to needle-type shapes as it has been shown, for example, by Turner et al [20] using SU-8 and Matsuzuka et al [21], who were using polymethyl methacrylate. Again, hollow structures suitable for microfluidic conduits within a sharp tip were not yet demonstrated by these authors.…”
Section: High Aspect-ratio Polymer Fabricationmentioning
confidence: 99%
“…To date, several studies have been reported on the removal of SU-8 by using reactive-ion-etching, downstream-chemical-etching, molten-salt-bath, and burning [14,25]. Although these methods are effective in terms of removal, they have several drawbacks: they all require expensive equipment and, except reactive-ion-etching, they damage the master-mold by lowering the mechanical strength and making the surface rough.…”
Section: Removal Of Su-8mentioning
confidence: 99%
“…To date, master-molds have been fabricated by a variety of techniques, which can be grouped into three categories ( Fig. 1): (i) direct fabrication, which includes mechanical machining [8,9], laser ablation [10], and electrodischarge-machining [11]; (ii) indirect fabrication from a mother-mold, which uses dry-etched silicon [12] or photolithographically (laser [13] and X-ray [14]) patterned polymers -the master-mold is fabricated from a mother-mold, by electroplating; and (iii) pseudo-direct fabrication using a photoresist [8,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation